A Multivariate Tobit Estimation of Rural Land Rental and Labor Market Participation Decisions of Farm Households in Ethiopia - Zegeye Tirfe (한국농촌경제연구원, 2018)
The paper tries to identify factors that affect rural households’ joint participation in rural labor and land rental markets. The study used a multivariate Tobit/mixed model that considers the existence of endogeneity and cross-equations interdependences to analyze rural land rental and labor markets. The estimation results show households who are well endowed with economically active labor force, oxen, a social network, and farming resources are more likely to participate as a tenant in land rental markets. Similarly, landless and near-landless households as well participate as a tenant in land rental markets. In contrast, households who are less endowed with farming skills and farming inputs are more likely to rent out their land and then engage in off-farm work. As a result, it is momentous to design a proper policy that promotes and reshapes the rural financial service for smallholder farmers for both on-farm and off-farm activities. We found that education is the most valuable asset for rural farm households to pursue opportunities in agriculture, obtain skilled off-farm work, and start a business in the rural non-farm economy. Yet, the education level in rural Ethiopia is very low. Hence, it is important to design appropriate basic adult educational programs, and open farmers training centers for rural farmers that promote technical and business skills in the agriculture and rural off-farm economy. Off-farm employments absorb surplus labor from agriculture. Hence, it is important to design appropriate policy in order to improve the rural off-farm economy in a rural part of the country. Finally, we recommend policy makers to see the off-farm economy as one component of rural growth and transformation strategy and remove any barriers that limit farmers’ entry to off-farm employments.
Keywords: 다변량 Tobit 모형; 농지 임대시장; 농촌노동시장; 내생성; multivariate Tobit model; rural land rental market; rural labor market; endogeneity